Emerging treatment options for nasopharyngeal carcinoma - Zhang L; Chen QY; Liu H; Tang LQ; Mai HQ (Dove Medical Press, 2013)
Lu Zhang,1,2 Qiu-Yan Chen,1,2 Huai Liu,1,2 Lin-Quan Tang,1,2 Hai-Qiang Mai1,21State Key Laboratory of Oncology in South China, 2Department of Nasopharyngeal Carcinoma, Sun Yat-sen University Cancer Center, Guangzhou, People's Republic of ChinaAbstract: Nasopharyngeal carcinoma is endemic in Asia and is etiologically associated with Epstein–Barr virus. Radiotherapy is the primary treatment modality. The role of systemic therapy has become more prominent. Based on multiple phase III studies and meta-analyses, concurrent cisplatin-based chemoradiotherapy is the current standard of care for locally advanced disease (American Joint Committee on Cancer manual [7th edition] stages II–IVb). The reported failure-free survival rates from phase II trials are encouraging for induction + concurrent chemoradiotherapy. Data from ongoing phase III trials comparing induction + concurrent chemoradiotherapy with concurrent chemoradiotherapy will validate the results of these phase II studies. Intensity-modulated radiotherapy techniques are recommended if the resources are available. Locoregional control exceeding 90% and reduced xerostomia-related toxicities can now be achieved using intensity-modulated radiotherapy, although distant control remains the most pressing research problem. The promising results of targeted therapy and Epstein–Barr virus-specific immunotherapy from early clinical trials should be validated in phase III clinical trials. New technology, more effective and less toxic chemotherapy regimens, and targeted therapy offer new opportunities for treating nasopharyngeal carcinoma.Keywords: nasopharyngeal carcinoma, intensity-modulated radiotherapy, chemoradiotherapy, molecular targeted agents, immunotherapy, prognostic markers